ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KECENDERUNGAN FRAUD - BAKU, AGUS; NURHIDAYAH, NURHIDAYAH (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2019)
The purpose of this study is to find out empirical verification of the influence of factors in attributive justice, procedural justice, interactional justice, enforcement of regulations, effectiveness of internal control, commitment and organizational ethical culture on fraud tendencies at the Marisa Sub-District Office, Pohuwato District. The analytical method used is multiple regression. The results showed that the majority of civil servants working in the Marisa Sub-District Office, Pohuwato District, perceive distributive justice, procedural justice and interactional justice to be in the fair category, regulation enforcement is in the very upright category, the effectiveness of internal control is in the very effective category, organizational commitment is in the very category of commitment and organizational ethical culture it is in the ethical category, while perceptions of the tendency of fraud are in the very rare category. The perception of distributive justice does not have a significant influence on the tendency of fraud. Perceptions of procedural justice did not have a significant influence on the tendency of fraud, meaning that the perception of civil servants in the Marisa Sub-District Office of Pohuwato District was related to procedural justice which was felt to not have an impact on the tendency of fraud. Perception of interactional justice has a negative and significant effect on the tendency of fraud, this result means that the higher the perception of civil servants in the Marisa Sub-District Office of Pohuwato District related to interactional justice, the lower the tendency of employees to commit fraud. Perception of regulation enforcement has a negative and significant effect on the tendency of fraud. Perception of the effectiveness of internal control has a negative and significant effect on the tendency of fraud. Perception of organizational commitment has a negative and significant effect on the tendency of fraud. Perceptions of organizational ethical culture have a negative and significant effect on trends in fraud. Penelitian ini bertujuan adalah untuk mengetahui memberikan verifikasi empiris pengaruh faktor keadilan ditributif, keadilan prosedural, keadilan interaksional, penegakan peraturan, keefektifan pengendalian intern, komitmen dan budaya etis organisasi terhadap kecenderungan fraud pada Kantor Camat Marisa Kabupaten Pohuwato. Metode analisis yang digunakan yaitu regresi berganda. Hasil penelitian menunjukkan Sebagian besar pegawai negeri sipil yang bekerja pada  Kantor Camat Marisa Kabupaten Pohuwato mempersepsikan keadilan distributif, keadilan prosedural dan keadilan interaksional berada dalam kategori adil, penegakan peraturan berada dalam kategori sangat tegak, keefektifan pengendalian internal berada dalam kategori sangat efektif, komitmen organisasi berada dalam kategori sangat komitmen dan budaya etis organisasi berada dalam kategori etis, sedangkan persepsi tentang kecenderungan kecurangan berada dalam kategori sangat jarang terjadi. Persepsi keadilan distributif tidak memiliki pengaruh yang signifikan terhadap kecenderungan kecuranganPersepsi penegakan peraturan berpengaruh negatif dan signifikan terhadap kecenderungan kecurangan. Persepsi keefektifan pengendalian internal berpengaruh negatif dan signifikan terhadap kecenderungan kecurangan. Persepsi komitmen organisasi berpengaruh negatif dan signifikan terhadap kecenderungan kecurangan. Persepsi budaya etis organisasi berpengaruh negatif dan signifikan terhadap kecenderungan kecurangan.